Work-family reconciliation policies and women's and mothers' labor market outcomes in rich democracies - David Brady; Agnes Blome; Julie A. Kmec (Luxembourg Income Study (LIS), 2018)
Prominent research has claimed that work-family reconciliation policies trigger "tradeoffs" and "paradoxes" in terms of gender equality with adverse labor market consequences for women. These claims have greatly influenced debates regarding social policy, work, family, and gender inequality. Motivated by limitations of prior research, we analyze the relationship between the two most prominent work-family reconciliation policies (paid parental leave and public childcare coverage) and seven labor market outcomes (employment, full-time employment, earnings, fulltime earnings, being a manager, being a lucrative manager, and occupation percent female). We estimate multi-level models of individuals nested in a cross-section of 21 rich democracies near 2005, and two-way fixed effects models of individuals nested in a panel of 12 rich democracies over time. The vast majority of coefficients for work-family policies fail to reject the null hypothesis of no effects. The pattern of insignificance occurs regardless of which set of models or coefficients one compares. Moreover, there is as much evidence that significantly contradicts the "tradeoff hypothesis" as is consistent with the hypothesis. Altogether, the analyses undermine claims that work-family reconciliation policies trigger tradeoffs and paradoxes in terms of gender equality with adverse labor market consequences for women.
Keywords: J; H; I; 330; work; family; labor markets; social policy; inequality; welfare state